Religion and the Art of Representation: Symbolism of Zoomorphic Style in Central Asia - Yerekesheva, Laura G. (The New Research of Tuva, 2021)
Zoomorphic images found in the large area of the Eurasian continent stretching from East Asia, South Siberia, Mongolia, Tuva, Altai and, Kazakhstan to the Volga region, the Urals, the Caucasus, the Black Sea region and associated with the Saka / Scythian cultures have both common typological patterns and their own specificity. It is well known that the Saka / Scythian zoomorphic style had an exceptionally strong impact on the cultures of the peoples of Central Asia, the echoes of which, through centuries, can be traced in the material culture of today.The article examines the issues of symbolic representation of religious ideas and beliefs in zoomorphic style of Central Asian art from the middle to second half – of the 1st millennium BC. Geographically and chronologically, the article focuses on artifacts and finds related to the so-called Saka period, such as reindeer stones and khereksurs, elements of horse harness, military equipment, jewelry and art in a zoomorphic style found in Tuva, Altai, and Semirechye.Methodologically, this representation is studied on the basis of a cross-disciplinary approach, using elements of the theory of structural functionalism in the theoretical sociology of religion (T. Parsons), and of a semiotic approach in culture (Yu. Lotman), both taken in their relation to levels of development and religious beliefs. It is shown that the zoomorphic style can reflect (to varying degrees) elements related to a most diverse multitude of belief systems, such as solar cults, Heaven cults, ancestor cults, zoomorphic cults, magic, totemism, and shamanism. It is concluded that the zoomorphic style in art and material culture is a synergistic representation of the most ancient and basic religious concepts in general; the result of a transformation of a sign, through information and meaning, into a symbol.
Keywords: symbolic representation; religious beliefs; Saka culture; Scythian culture; solar cults; ancestor cult; totemism; shamanism; zoomorphic style; Central Asia; Tuva; Arzhan burial mounds; Altai; Pazyryk burial mound; Semirechye